Simulating the trajectories of one-dimensional pseudoparticles with parallel agents - Pabico, Jaderick P. (Philippine computing journal)
This paper presents a mechanism for multiple agents that dynamically load-balance the parallel computation of quantum trajectories of an one-dimensional free particle using the quantum trajectory method. The agents are able to improve the simulation time by dynamically load-balancing the parallel computation of the trajectories. The load imbalance introduced by the parallel runtime system and by the computationally-intensive trajectories of the pseudoparticles is reduced by the agents at higher number of processors. Results of experiments on a multi-purpose message-passing cluster are presented to confirm that the agents achieve better simulation performance than with the current load balancing techniques at higher number of processors.